UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE SISWA KELAS VIID SMP N 1 SRUMBUNG KABUPATEN MAGELANG - Fibriana Ayukmartina; A. A Sujadi; Agustina Sri Purnami (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
The purposes of this study was to improve liveliness and mathematics achievement students VIID in junior high school 1 Srumbung Magelang with cooperative learning TPS (Think Pair Share). This research is Classroom Action Research (CAR). The subjects in this study were students of class VII D which is 34 students who comprised 18 male students and 16 female students. The objects of this research are being active and increase math achievement. It is shown by an increase in the average yield percentage of being active student learning based on the observation sheet. The first cycle was 53,91% became 75,97% in cycle II.